1969
DOI: 10.1111/j.1365-2621.1969.tb12104.x
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, Identification and Comparison of the Volatiles of Peach Fruit as Related to Harvest Maturity and Artificial Ripening

Abstract: SUMMARY: Volatiles of peach (Prunus persica L., cultivar, Gleason Early Elberta) fruit were studied by gas‐liquid chromatography, thin‐layer chromatography and infrared spectrometry. Chromatograms of the volatiles of hard‐mature, firm‐mature, soft‐mature, tree‐ripe and artificially ripened, hard‐mature fruit were obtained with temperature programing and flame ionization detection. The volatile concentrates of tree‐ripe peaches produced 86 peaks. The major peaks were isolated and the infrared spectra determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
55
4
1

Year Published

1978
1978
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(65 citation statements)
references
References 12 publications
5
55
4
1
Order By: Relevance
“…The composition and content of volatile aromas change during the maturation. In immature fruits, C 6 compounds are the major contributors, but their levels decrease drastically whilst those of lactones, benzaldehyde and linalool increase significantly during maturation (Do et al, 1969;Engel et al, 1988b). Several studies have also investigated the effect of culture techniques and management on composition and content of volatiles.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…The composition and content of volatile aromas change during the maturation. In immature fruits, C 6 compounds are the major contributors, but their levels decrease drastically whilst those of lactones, benzaldehyde and linalool increase significantly during maturation (Do et al, 1969;Engel et al, 1988b). Several studies have also investigated the effect of culture techniques and management on composition and content of volatiles.…”
Section: Introductionmentioning
confidence: 97%
“…The relative contributions of specific aroma volatile compounds to the flavour of peaches and nectarines have been examined by many investigators and more than 100 compounds have been identified (Aubert, Günata, Ambid, & Baumes, 2003;Aubert & Milhet, 2007;Chapman, Horvat, & Forbus, 1991;Derail, Hofmann, & Schieberle, 1999;Engel, Ramming, Flath, & Teranashi, 1988b;Jia, Okamoto, & Hirano, 2004;Kakiuchi & Ohmiya, 1991;Lavilla, Recasens, & Lopez, 2001;Robertson, Meredith, Horvat, & Senter, 1990a;Takeoka, Flath, Guntert, & Jennings, 1988). The volatiles of peaches and nectarines include C 6 compounds, alcohols, aldehydes, esters, terpenoids, ketones and lactones, among which the lactones, particularly c-and d-decalactones, have been reported to be the major contributors to peach aroma with smaller contributions by other volatiles such as C 6 aldehydes, alcohols and terpenoids (Do, Salunkhe, & Olson, 1969;Engel et al 1988a;Horvat et al 1990b;Visai & Vanoli, 1997).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…The most abundant compound is c 6 compound, linalool, benzaldehyde, ester terpinoids, c 13 norisoprenoids, ketones and lactones [90], [91]. The flowering properties derive from lactones and particularly γ & δ-decalactones, with smaller contributions from C 6 aldehydes, alcohols, terpinoids [92], [93], [94]. The chemical composition of the volatile compound varies in the different part of the fruit.…”
Section: Volatile In Naturementioning
confidence: 99%
“…Durante el almacenamiento se observó un ligero aumento de estos compuestos volátiles como consecuencia del proceso propio de maduración y senescencia (Do et al, 1969;Robertson et al, 1990), siendo más importante el aumento del nivel de etanol que el del acetaldehído. La variedad de albaricoque Llíria, en una de las campañas estudiadas, fue la que presentó mayores valores de etanol, tanto en el momento de recolección (30 mg/100 ml) como tras los distintos periodos de almacenamiento estudiados (≈ 200 mg/100 ml).…”
Section: Fruta De Hueso: Melocotón Nectarina Y Albaricoqueunclassified